Culture Of Architectural Firms In Nigeria: An Exploratory Study - Oluwatayo, Adedapo Adewunmi; Amole, Dolapo (Penerbit Universiti Sains Malaysia, 2012)
What is the culture of an architectural firm, and what are the organisational characteristics that shape this culture? These are the questions addressed by this paper that surveys 92 Nigerian architectural firms. The study investigated the culture of these architectural firms using the response of the firms' principals to a questionnaire of value statements regarding innovation, stability, people orientation, outcome orientation, team orientation and aggressiveness. The culture types were determined using a two-step cluster analysis of the data. Categorical regression was also used to determine the factors that shaped a firm's culture. The study revealed that the architectural firms did not have either market or hierarchical cultures. The findings also challenged the notion that larger firms tend to be more impersonal. However, the predominance of responsive and staff-oriented cultures confirmed the notion that service sector organisations are more people-oriented than outcome-oriented confirms. The leadership style of the principals best predicted a firm's culture.